Clinical Phenotype of Musladin‐Lueke Syndrome in 2 Beagles. (3rd February 2017) - Packer, R.A.; Logan, M.A.; Guo, L.T.; Apte, S.S.; Bader, H.; O'Brien, D.P.; Johnson, G.; Shelton, G.D.
Abstract : Musladin‐Lueke syndrome (MLS), previously termed Chinese Beagle syndrome, is an autosomal‐recessive connective tissue disorder characterized by extensive fibrosis of the skin and joints that was first identified in Beagles in the 1970s. Recent research identified a founder mutation (c.660C>T; p.R221C) in the ADAMTSL2 gene in Beagles with MLS. Here, we report the detailed clinical phenotype and laboratory findings in 2 Beagles affected with MLS. We discuss these findings in relation to the human disorder geleophysic dysplasia (GD), which also arises from recessive ADAMTSL2 mutations, and recent findings in Adamtsl2 ‐deficient mice.